The Role of ECOWAS in Peace, Security, and Sustainable Development in West Africa Region - Agbebaku, Professor P. E; Uwa, Osimen Goddy; J.O Fayeye, Professor, (IJRDO - Journal of Social Science and Humanities Research, 2018)
Of the many challenges facing Africa, the quest for peace, security and sustainable development is undoubtedly the most pressing issues. So many African countries are still trapped in a vicious circle of conflict and insecurity with its attendant consequence. The African Union (AU), ECOWAS and its people are deeply concerned about the emerging trend of election-related conflicts and violence, the resurgence of coups d’état and other forms of unconstitutional change of government occurring on the continent including the manipulations of constitutions and electoral laws in violation of constitutional provisions, as well as the Boko Haram wave of attacks in Nigeria. The consequences of armed conflicts in Africa’s socio-economic development have been very glaring. The effects of armed conflicts as well as other types of violence continue to establish the true extent of this interconnectedness. The resurgence of buying and selling of human beings or human trafficking in sub Sahara Africa has shown the level of insecurity and poverty in the continent. Africa has witnessed a number of long-term, severe and, in some cases, inter-related crises and violent conflicts. The mass proliferation of arms in the Sahel-Sahara belt in Africa following the Libyan uprising constitutes a major challenge for peace and security. Peace, security and sustainable development in Africa cannot be taken for granted. The most significant issue that brings to bear the establishment of ECOWAS was based on member States to cooperate among themselves for the purpose of promoting economic growth and integration. However, after many years the sub- regional establishment still faced with challenges in relation to sustainable development, peace and security matters to which it was established .It on this backdrop, therefore, the paper look at the role of ECOWAS in creating an enabling environment where peace and security is sustainable for West African states to engineer sustainable development through regional integration and economic co-operation among the countries in West Africa. The methodology used in this work is review of previous literature and the use of content analysis which will also provide useful information on how peace, security and sustainable development can be achieved in the region of West Africa. The findings from this study reviews that, peace and security sustainability can only be guaranteed when the West African States employ the measures that would lead to economic growth and development of the region through provision of job opportunities to the youths, provision of adequate and trained security personnel that would help to monitor the porus border, Proper mechanisms for conflict resolution, management and peace- building to foster and promote peace within the region, transparency and accountability in governance and good leadership to foster growth and development in the region of ECOWAS community and among others.